Relapse to Smoking and Postpartum Weight Retention Among Women Who Quit Smoking During Pregnancy - Levine, Michele D. (2011)
Postpartum weight retention contributes to obesity risk in women. Given that most women who quit smoking as a result of pregnancy will resume smoking within 6 months postpartum and that there is a robust association between smoking and weight, we sought to evaluate postpartum weight retention as a function of postpartum smoking status among women who had quit smoking during pregnancy. Women (N = 183) with biochemically confirmed cigarette abstinence at the end of pregnancy were recruited between February 2003 and November 2006. Women self-reported demographic information and weight before pregnancy. Smoking status and weight were documented at the end of pregnancy and at 6, 12, and 24 weeks postpartum. Breastfeeding was reported at 6 weeks postpartum. Differences in weight retention by relapse status at each assessment were evaluated. To examine weight retention in the presence of conceptually relevant covariates, mixed models with log-transformed weight data were used. At 24 weeks postpartum, 34.6% of women remained abstinent. Women who remained abstinent throughout the 24-week period retained 4.7 ± 2.1 kg more than did women who had relapsed by 6 weeks postpartum, P = 0.03. This difference in postpartum weight retention was significant after controlling for relevant covariates (age, race, breastfeeding, and pregravid BMI). Resumption of smoking within the first 6 weeks following childbirth is associated with decreased postpartum weight retention, even after controlling for breastfeeding and pregravid weight. Interventions to sustain smoking abstinence postpartum might be enhanced by components designed to minimize weight retention.